Financial mindset, entrepreneurial mindset, and personal finance of university students - Aplonia Atto; Ariyon Stefen Ndun (Universitas Negeri Surabaya, 2019)
The purpose of the research is identifying the influence of financial mindset and entrepreneurial mindset to personal finance. This is a quantitative research with descriptive analysis and simple linear regression analysis. The researchs respondents are eighty one (81) students of Faculty of Economics, Universitas Persatuan Guru 1945 NTT. The sampling technique is random sampling with questionnaire as data collection method. The research instrument for financial mindset is adopted from œOTM The Knew Rules of Building Wealth (CNBC) by Rhodes (2010) and the entrepreneurship mindsets instrument is adopted from ˜Building E-Businesses series and Personal finance by Spinela, Yang & Laster (2007). The results imply that both financial mindset and entrepreneurial mindset have significant and simultaneous influence to personal finance.KeywordsFinancial mindset; entrepreneurial mindset; personal finance